Assessment of free fatty acids and cholesteryl esters delivered in liposomes as novel class of antibiotic. (December 2016) - Cheung Lam, Annie; Sandoval, Natalie; Wadhwa, Ritambhara; Gilkes, Janine; Do, Thai; Ernst, William; Chiang, Su-Ming; Kosina, Suzanne; Howard Xu, H.; Fujii, Gary; Porter, Edith
Abstract Background Healthcare associated infections (HAI) with multidrug-resistant (MDR) bacteria continue to be a global threat, highlighting an urgent need for novel antibiotics. In this study, we assessed the potential of free fatty acids and cholesteryl esters that form part of the innate host defense as novel antibacterial agents for use against MDR bacteria. Methods Liposomes of six different phospholipid mixtures were employed as carrier for six different fatty acids and four different cholesteryl esters. Using a modified MIC assay based on DNA quantification with the fluoroprobe Syto9, formulations were tested against Gram-positive and Gram-negative bacteria implicated in HAI. Formulations with MIC values in the low μg/mL range were further subjected to determination of minimal bactericidal activity, hemolysis assay with sheep erythrocytes, and cytotoxicity testing with the human liver cell line HepG2. The potential for synergistic activity with a standard antibiotic was also probed. Results Palmitic acid and stearic acid prepared in carrier 4 (PA4 and SA4, respectively) were identified as most active lipids (MIC against MDRStaphylococcus epidermidis was 0.5 and 0.25 μg/mL, respectively; MIC against vancomycin resistantEnterococcus faecalis (VRE) was 2 and 0.5 μg/mL, respectively). Cholesteryl linoleate formulated with carrier 3 (CL3) exhibited activity against theS. epidermidis strain (MIC 1 μg/mL) and aPseudomonas aeruginosa strain (MIC 8 μg/mL) and lowered the vancomycin MIC for VRE from 32–64 μg/mL to as low as 4 μg/mL. At 90 μg/mL PA4, SA4, and CL3 effected less than 5 % hemolysis over 3 h and PA4 and CL3 did not exhibit significant cytotoxic activity against HepG2 cells when applied at 100 μg/mL over 48 h. Conclusions Our results showed that selected fatty acids and cholesteryl esters packaged with phospholipids exhibit antibacterial activity against Gram-positive and Gram-negative bacteria and may augment the activity of antibiotics. Bactericidal activity could be unlinked from hemolytic and cytotoxic activity and the type of phospholipid carrier greatly influenced the activity. Thus, fatty acids and cholesteryl esters packaged in liposomes may have potential as novel lipophilic antimicrobial agents.